Social Values Reflections Through the Use of EFL Storytelling: An Action Research with Primary Students - Claudia Milena Gómez Combariza; María Ximena Rodríguez Chapetón; Vanessa Alejandra Rojas Rincón (Asociación Colombiana de Profesores de Ingles, 2013)
This article reports on the results of an action research project carried out with a group of third graders at a public school in Bogotá. The project aimed to gain insights into the use of English as foreign language storytelling and to analyze the way in which students reflect upon their own social values. The findings suggest that the use of storytelling contributes to students' awareness about their behaviors by helping them to be critical of their role as students and citizens in school and the family community. It was also found that students' families play an integral role when students build their own basis for individual and social development.